If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x = 11 + 3x Solving 3 + 5x = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 5x + -3x = 11 + 3x + -3x Combine like terms: 5x + -3x = 2x 3 + 2x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 2x = 11 + 0 3 + 2x = 11 Add '-3' to each side of the equation. 3 + -3 + 2x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 11 + -3 2x = 11 + -3 Combine like terms: 11 + -3 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 5(x+10)2x=246 | | 3x*2xy+xy= | | A=6(2x-3)+2(3-2x) | | x^2=100+10x | | 6×1/2-7 | | 2x+35=5x-85 | | 10k=4k-16 | | y=2+3x+6x^2 | | 1/2x=34=48 | | 10x+2(141x)=-2 | | -12c=4c+12 | | 0.2(x+3)+0.5=0.2x-1.1 | | 7k-3k+11= | | 3/4×59×250 | | 8x-13/8=347/72 | | A=10(x-1)-2x | | -4x+14+6x-23=6 | | 3x+4?4=31 | | y=6x^2+3x+2 | | 5x^2-21x=24 | | -1/4b=-1 | | 4(-4x-4)=-8(8+2x) | | x×3/4×5/9=250 | | -6(m+20)=-3 | | 10x=5.3 | | c=5(x-4)+3x+2 | | -6x+9+8x=4 | | 3x+4-2(x+1)=9 | | -6+9+8x=4 | | 8(x+4)=6(x+10) | | -16x^2+40=0 | | 9z-9=-9 |